Multinational Enterprises and Corporate Labor Share - Adachi, Daisuke; Saito, Yukiko U. (The Review of Economics and Statistics, 2025)
Abstract This study analyzes how multinational enterprises (MNEs) influence corporate labor share in their home countries, using the 2011 Thailand Floods as a natural experiment. Flood-related disruptions to Thai subsidiaries of Japanese MNEs generated a negative foreign productivity shock that raised labor share in Japan. We interpret this pattern using a model with international factor substitution and estimate the elasticity of substitution between domestic labor and foreign inputs using an instrument based on flood exposure. The estimated model quantifies the long-run e!ect of Thai productivity growth on Japan's labor share, indicating that expanding global production networks can shift labor–capital balances.